AS ANASTÁCIAS DO QUILOMBO: Uma análise da participação e representação da mulher no hip-hop maranhense - DURANS, Claudimar Alves (2014)
This work aims to understand the participation and the social representations of the woman built by hip-hop Maranhão, in particular by the Group of women of Hip Hop movement – "black Anastasia", part of the hip-hop Movement Organized of Maranhão "Quilombo Urbano". You want to analyze, as the political-cultural movement, bringing together three artistic events: rap, break and graphite have treated gender relations in your interior, represented women and developing activities in order to build the ethnic-racial identity and gender to women who participate in it. To do so, We understand the hip-hop as a resistance movement and protest from its origins in American black ghettos has been formed by people whose identities are stigmatized, but have (re) and (re) built their ethnic and racial identities and gender, Deconstructing and subverting the dominant patterns of ethnic belonging and masculinity. While methodology, the study was conducted by the combination of bibliographical research, documentary and empirical, which led to the insertion of the researcher researched group. The analyses are based on theoretical considerations about HipHop, identity, gender relations and representation of women. The data reflected were collected through semi-structured interviews, participant observation, as well as the acquisition of documents, letters, pamphlets, newspapers and various other materials used and produced by hip-hop, in particular. We understand that hiphop is, despite all its contradictions, in a possibility for women seeking a collective action questioning the slighted positioning that is assigned to These, from a feminist claim building paths to greater cultural and political visibility.